African Swine Fever Virus as a Difficult Opponent in the Fight for a Vaccine—Current Data - Hanna Turlewicz-Podbielska; Anna Kuriga; Rafał Niemyjski; Grzegorz Tarasiuk; Małgorzata Pomorska-Mól (Viruses, 2021)
Prevention and control of African swine fever virus (ASFV) in Europe, Asia, and Africa seem to be extremely difficult in view of the ease with which it spreads, its high resistance to environmental conditions, and the many obstacles related to the introduction of effective specific immunoprophylaxis. Biological properties of ASFV indicate that the African swine fever (ASF) pandemic will continue to develop and that only the implementation of an effective and safe vaccine will ensure a reduction in the spread of ASFV. At present, vaccines against ASF are not available. The latest approaches to the ASFV vaccine’s design concentrate on the development of either modified live vaccines by targeted gene deletion from different isolates or subunit vaccines. The construction of an effective vaccine is hindered by the complex structure of the virus, the lack of an effective continuous cell line for the isolation and propagation of ASFV, unpredictable and stain-specific phenotypes after the genetic modification of ASFV, a risk of reversion to virulence, and our current inability to differentiate infected animals from vaccinated ones. Moreover, the design of vaccines intended for wild boars and oral administration is desirable. Despite several obstacles, the design of a safe and effective vaccine against ASFV seems to be achievable.